Cross-class metallo-β-lactamase inhibition by bisthiazolidines reveals multiple binding modes - Hinchliffe, Philip (2016)
Metallo-β-lactamases (MBLs) hydrolyze almost all β-lactam antibiotics and are unaffected by clinically available β-lactamase inhibitors (βLIs). Active-site architecture divides MBLs into three classes (B1, B2, and B3), complicating development of βLIs effective against all enzymes. Bisthiazolidines (BTZs) are carboxylate-containing, bicyclic compounds, considered as penicillin analogs with an additional free thiol. Here, we show both L- and D-BTZ enantiomers are micromolar competitive βLIs of all MBL classes in vitro, with Ki sof6-15 μM or 36-84 μM for subclass B1 MBLs (IMP-1 and BcII, respectively), and 10-12 μM for the B3 enzyme L1. Against the B2 MBL Sfh-I, the L-BTZ enantiomers exhibit 100-fold lower Ki s (0.26-0.36 μM) than D-BTZs (26-29 μM). Importantly, cell-based time-kill assays show BTZs restore β-lactam susceptibility of Escherichia coli-producing MBLs (IMP-1, Sfh-1, BcII, and GOB-18) and, significantly, an extensively drug-resistant Stenotrophomonas maltophilia clinical isolate expressing L1. BTZs therefore inhibit the full range of MBLs and potentiate β-lactam activity against producer pathogens. X-ray crystal structures reveal insights into diverse BTZ binding modes, varying with orientation of the carboxylate and thiol moieties. BTZs bind the di-zinc centers of B1 (IMP-1; BcII) and B3 (L1) MBLs via the free thiol, but orient differently depending upon stereochemistry. In contrast, the L-BTZ carboxylate dominates interactions with the monozinc B2 MBL Sfh-I, with the thiol uninvolved. D-BTZ complexes most closely resemble β-lactam binding to B1 MBLs, but feature an unprecedented disruption of the D120-zinc interaction. Cross-class MBL inhibition therefore arises from the unexpected versatility of BTZ binding.